Social Movement Theory, Collective Action Frames and Union Theory: A Critique and Extension. (21st August 2012) - Gahan, Peter; Pekarek, Andreas
Abstract: The publication of John Kelly's Rethinking Industrial Relations in 1998 spawned a growing interest among researchers in exploring how social movement (SM) theory can be used to inform union research, particularly in the context of revitalization/renewal debates. Our starting proposition is that this approach can be extended through an engagement with the larger corpus of SM theory. We focus in particular on the 'collective action frame' concept. Drawing on examples used by SM scholars, we illustrate how these concepts can be used to extend and enrich union theory and pose new questions concerning the role of unions.